2014
DOI: 10.1007/s11943-014-0142-9
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of unit non-response in the Ifo Business Survey

Abstract: It is well-known that non-response affects the results of surveys and can even cause biases due to selectivities if it cannot be regarded as missing at random. In contrast to household surveys, response behaviour in business surveys is rarely examined in literature. This paper analyses a large business survey at a microdata level for unit non-response. The data base is the Ifo Business Survey, which was established in 1949 and is completed by more than 5000 firms every month. The panel structure makes it possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…This finding is consistent with previous observations (Mullner et al, 1981). Interestingly, studies conducted in nonhealth-care settings (Gupta, Shaw, & Delery, 2000; Phipps & Jones, 2007; Seiler, 2014; Tomaskovic-Devey et al, 1994) demonstrated an inverse relationship between organization size and RL, which contrast with our finding. The inverse relationship was interpreted by the earlier investigators to reflect the greater propensity for information dispersal and higher organizational complexities of larger organizations and by extension a lower capability and motivation to respond.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with previous observations (Mullner et al, 1981). Interestingly, studies conducted in nonhealth-care settings (Gupta, Shaw, & Delery, 2000; Phipps & Jones, 2007; Seiler, 2014; Tomaskovic-Devey et al, 1994) demonstrated an inverse relationship between organization size and RL, which contrast with our finding. The inverse relationship was interpreted by the earlier investigators to reflect the greater propensity for information dispersal and higher organizational complexities of larger organizations and by extension a lower capability and motivation to respond.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, Seiler and Heumann (2013) provide a statistical analysis of different imputation methods and conclude that the bias due to non-response does not significantly reduce the forecasting performance of the ifo Business Climate Index that is based on the micro data of the IBS. In addition, see Seiler (2014) for a more detailed analysis on the determinants of non-response in the IBS.…”
Section: Resultsmentioning
confidence: 99%
“…The most prominent example is establishment size. Most studies find that larger establishments are less likely to participate in surveys than smaller ones (Janik and Kohaut 2012;Earp et al 2018;Hecht et al 2019;König et al 2021;Küfner et al 2022), with some exceptions for surveys that implement special treatments on larger establishments, including adaptive recruitment strategies (Davis and Pihama 2009;Seiler 2014). Nonresponse biases are also found for industry type (Tomaskovic-Devey et al 1995), survey topic (HMRC 2010Snijkers et al 2013;Snijkers 2018;Küfner et al 2022), establishment age (Phipps and Jones 2007), average wages (Phipps et al 2012;Küfner et al 2022), and region of the establishment (Janik 2011;König et al 2021), among others.…”
Section: Nonresponse Bias In Establishment Surveysmentioning
confidence: 99%